Overcapacities in banking: Measurements, trends and determinants - Sándor Gardó; Benjamin Klaus (European Central Bank (ECB), 2019)
The prolonged crisis exposed the vulnerability of a monetary union without a banking union. The Single Supervisory Mechanism (SSM), which started operating in November 2014, is an essential step towards restoring banks to health and rebuilding trust in the banking system. The ECB is today responsible for setting a single monetary policy applicable throughout the euro area and for supervising all euro area banks in order to ensure their safety and soundness, some directly and some indirectly. Its role in the area of financial stability has also expanded through the conferral of macroprudential tasks and tools that include tightening national measures when necessary. It thus carries out these complementary functions, while its primary objective of pursuing price stability remains unchanged. What are the working arrangements of this enlarged ECB, and what are the similarities and existing synergies among these functions? In the following pages, focusing on the organisational implications of the "new" ECB, we show the relative degrees of centralisation and decentralisation that exist in discharging these functions, the cycles of policy preparation and the rules governing interaction between them.
Keywords: E42; E58; F36; G21; 330; overcapacity; bank size; bank competition; efficiency; composite indicator